THE INFLUENCE OF SCRIPTED GAME TASKS ON FUNCTIONAL LITERACY IN TEACHING BIOLOGY - Dilmurat Aizhanar; Anargul Sailaubekovna Sharipkhanova (World Scientific Reports, 2026)
The article examines the influence of scenario-based game tasks on the development of students’ functional literacy in biology education. The study was conducted among 10th-grade students based on the ecology unit of the biology curriculum. Scenario-based game activities such as “Environmental Court,” “Saving the Ecosystem,” and “Environmental Debate” were implemented during the experimental instruction. The primary aim of the research was to determine the impact of game-based tasks on students’ ability to apply biological knowledge in real-life situations, analyze ecological problems, and make practical decisions. The pedagogical experiment method was employed in the study, and the results of the control and experimental groups were comparatively analyzed. The findings demonstrated that scenario-based game tasks effectively contribute to the development of students’ cognitive, analytical, practical-applied, and communicative skills. In addition, game technologies were found to increase students’ interest in the subject and activate their learning engagement. The results of the study provide a basis for considering scenario-based game tasks in biology education as an effective methodological tool for the development of functional literacy